Physical Activity and Heart Rate Variability Among Middle Age to Older Adults with Heart Failure: The State of Science - Prakobchai, Sattha; Suwan, Kijja; Dechakul, Manida (Journal of Food Health and Bioenvironmental Science, 2024)
Physical activity or exercise relates to the physiological responses especially in heart rate variability (HRV). HRV is a predictor of prognosis of heart failure and cardiac functions. However, little is known about the relationship of physical activity, HRV improvement and autonomic regulation in heart failure of older adults.The purpose of this state of science review is to synthesize the evidence that shows the effects of physical activity or exercise, HRV and physiological outcomes. The literature searched includes 12 studies from four electronic databases (PsycInfo, Pubmed, Scopus and CINAHL). The findings revealed that physical activity or exercise will improve HRV. This review showed that physical activity improves cardiac autonomic function (nerohormornal activation, sympathetovocal balance, baroreceptor reflex) and inhibits alpha 2 antagonist to improve HR reserve and RR intervals and prevent premature ventricular contraction (PVC). However, the level of physical activity and intensity are not clear. Tailored interventions or community-based programs will be effective in order to maintain physical activity and functional outcomes. A higher HRV is related to the functional capacity compared to the lower. Therefore, healthcare providers should regularly assess heart rate variability among heart failure patients to determine the threshold and recovery for physical functioning in regards to the stress form physical activity.